"Locoregional perforator flaps in breast reconstruction: An anatomic review & quadrant algorithm". Issue 4 (April 2022) - Chartier, Christian; Safran, Tyler; Alhalabi, Becher; Murphy, Amanda; Davison, Peter
Abstract: Background: Plastic surgeons' firm grasp of perforator anatomy allows them to be increasingly mindful of esthetic outcomes, patient satisfaction, and donor-site function when approaching breast reconstruction. Mindfulness of these outcomes has contributed to the widespread use of locoregional perforator flaps in post-mastectomy and post-BCS reconstruction. Methods: A literature search of the PubMed database was performed to identify relevant studies reporting the use of locoregional perforator flaps in post-mastectomy breast reconstruction. Selected manuscripts were analyzed and grouped by pedicled flap category. Articles were additionally assessed for the advantages and disadvantages of each flap and reported complications. Results: Following three rounds of review, 30 of 101 (29.7%) articles were retained as specifically pertinent to the use of locoregional flaps in breast reconstruction surgery. They were categorized by locoregional perforator flap used (TDAP, LICAP, AICAP, LTAP, or IMAP). In total, the included studies reported on the use of perforator flaps in 829 patients, with complications occurring in 73 of 418 patients (17.5%). Commonly reported complications across all included studies were hematomas ( n = 10), infection ( n = 7), fat necrosis/steatofibrosis ( n = 31), extruded expanders ( n = 1), dehiscence ( n = 2), seroma ( n = 2), required cosmetic correction of the donor area ( n = 5), flap congestion ( n = 11), flap failure ( n = 2), poor esthetic outcome ( n = 4), grade II capsular contracture ( n = 3, all of whom received postoperative radiation), and keloid scars( n = 1). Conclusions: Though the available literature remains anecdotal, locoregional flap-based reconstruction may provide some benefit in post-BCS reconstruction by sparing donor-site musculature and nerve supply and by minimizing adverse events